Legal Protection for Doctors in the Implementation of Therapeutic Agreements in Informed Consent Based on the Principles of Consensualism and Pacta Sunt Servanda at Ibnu Sina Islamic Hospital Bukittinggi - Ikhsan, Muhammad; Januardi , Hengki; Satria, Andrea Octorayama (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to deconstruct and conduct an in-depth analysis of legal protection for medical personnel, particularly doctors, within the framework of therapeutic agreements through the mechanism of informed consent. This study specifically evaluates the implementation of two fundamental principles in civil law, namely the principle of consensualism and the principle of pacta sunt servanda, in the Emergency Department of Ibnu Sina Islamic Hospital Bukittinggi. The main challenge identified is the complexity of medical decision-making in emergency situations, where formal procedures are often constrained by limited time and the critical condition of patients. The research method employed is normative juridical with a qualitative approach, utilizing primary data from interviews and secondary data from legal literature and recent regulations, including Law Number 17 of 2023 concerning Health. The findings reveal that in emergency situations, doctors apply the doctrine of implied consent as a manifestation of the principle of consensualism. The legal relationship formed is subsequently binding based on the principle of pacta sunt servanda as an obligation of effort (inspanningverbintenis) in accordance with professional standards. Legal protection for doctors is both preventive and repressive in nature. Preventive protection is achieved through compliance with Standard Operating Procedures (SOP) and proper medical record documentation, while repressive protection is realized through the use of such documentation as valid evidence to counter allegations of malpractice.